The Ugly Duckling - Retold by Davidson, Susanna (London Usborne Publishing Ltd, 2006)
Tells the story of The Ugly Duckling. Suitable for children just beginning to read, this title is part of the Usborne English Language Learners programme, featuring books from the Usborne Reading Programme, with audio CDs in British and American English, downloadable worksheets and teacher's notes.
Include Color Illustration
Keywords: Ducks -- Self-acceptance -- Swans